Case report: A girl with witnessed sleep apnea - Shuai Wu; Waner Wang; Fang Han; Liyue Xu (Frontiers in Neurology, 2024)
IntroductionPfeiffer syndrome is a rare genetic disorder characterized by craniosynostosis, broad thumbs and big toes, and partial syndactyly of the hands and feet. This case report presents the case of a girl diagnosed with type 2 Pfeiffer syndrome who experienced severe obstructive sleep apnea (OSA).Case reportThe patient had been using an oropharyngeal airway since the age of 4 months due to snoring and witnessed apnea during sleep. At 11 months old, she was referred to our sleep clinic because of growth limitation and gross motor ability issues. Polysomnography (PSG) showed severe obstructive hypopnea before any treatment, and revealed severe central sleep apnea with the oropharyngeal airway in place. Positive airway pressure (PAP) therapy was initiated, which improved both her sleep and gross motor ability.ConclusionThis case report emphasizes the importance of thorough sleep studies for diagnosing sleep and breathing disorders in Pfeiffer syndrome patients and highlights the effectiveness of PAP therapy in managing these conditions.